ASSOCIATION REPORTS. - Blough, Carman G. (The Accounting Review, 1944)
Abstract The article presents information on the American Accounting Association's annual meeting to be held from September 8-9, 1944, in Chicago, Illinois and the program to discuss various vital subjects including impacts of war. Tentative plans for a discussion of the termination of war contracts, a subject that is already of vital importance to businessmen and their accountants. As changes in war needs develop, necessitating cutbacks and contract cancellations while one is still actively in the war, increasingly large numbers of businesses will be affected and as one approach and reach the end of the war the problems will be tremendous. Persons who are active in establishing and executing the policies of termination for the government will be on the program, as well as representatives of industries which are materially affected. Of special interest to both teachers and practitioners, is the subject of post-war education in accounting. In that connection it is planned to have discussions of such subjects as refresher courses for returning accountants; the possibility of an accelerated training program along the line developed by the Army and the Navy; possibilities of visual instruction; general requirements essential to a successful professional career.